Synergistic properties of β-Ga2O3 nanowire arrays - Naumenko, M.V.; Balabai, R.M. (Physics and Chemistry of Solid State, 2023)
Using the methods of electron density functional and ab initio pseudopotential, the spatial distributions of valence electron density, the density of electronic states and Coulomb potentials along the specified directions within the arrays of β-Ga2O3 nanowires with different cross-sectional shapes and positions in arrays were calculated. Synergistic properties of arrays of wires are established. The degree of influence of the wires on each other is determined depending on the geometric parameters of their mutual location in the array The electronic characteristics of the array of wires as a whole are determined.